Recoding Life Information and the Biopolitical - Tamminen, Sakari (Taylor & Francis, 2018)
This book addresses the unprecedented convergence between the digital and the corporeal in the life sciences and turns to Foucault's biopolitics in order to understand how life is being turned into a technological object. It examines a wide range of bioscientific knowledge practices that allow life to be known through codes that can be shared (copied), owned (claimed, and managed) and optimised (remade through codes based on standard language and biotech engineering visions).